Responsibility of Serbia for genocide: Application of the Convention on the prevention and punishment of the crime of genocide - Tejić Mirjana (Temida)
On February 26th 2007, International Court of Justice claimed Serbia responsible for failing to prevent genocide and punish perpetrators underlining its' responsibility to cooperate with International Criminal Tribunal for former Yugoslavia. Although it was confirmed genocide has been committed in Srebrenica 1995, Serbia is not obliged to pay financial reparations. Judgment makes distinction between individual and three-fold state responsibility for genocide, based on Convention on the Prevention and Punishment of the Crime of Genocide and other sources of international law. There are evident disagreements among judges on jurisdiction, interpretation rules, even on meritum of the case. Many questions still remain open especially what precedent effects will have on establishment of state's dolus specialis and how it will influence the reconciliation process in the region.